1986
DOI: 10.1182/blood.v67.3.811.811
|View full text |Cite
|
Sign up to set email alerts
|

Mixed hematologic chimerism after allogeneic marrow transplantation for severe aplastic anemia is associated with a higher risk of graft rejection and a lessened incidence of acute graft-versus-host disease

Abstract: Ninety-six patients with severe aplastic anemia who received a sex- mismatched, HLA-identical allogeneic sibling marrow transplant had sequential cytogenetic analyses performed to determine the incidence and implications of posttransplant mixed hematologic chimerism. Of the 96 patients, 56 (58.3%) became mixed chimeras with coexisting host and donor cells detected in peripheral blood or marrow 14 days or later after transplant, and 40 patients (41.7%) were complete chimeras with 100% donor-type hematopoietic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
2
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(34 citation statements)
references
References 26 publications
1
30
2
1
Order By: Relevance
“…A small number of studies have assessed chimerism in SAA or FA with results on significant numbers of patients. Hill et al (1986) reported on a group of 96 patients who received SCT for SAA with a conditioning regimen that did not include irradiation. Cytogenetic analysis was performed and indicated a high level of MC (56 of 96 patients) in the first year post-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have assessed chimerism in SAA or FA with results on significant numbers of patients. Hill et al (1986) reported on a group of 96 patients who received SCT for SAA with a conditioning regimen that did not include irradiation. Cytogenetic analysis was performed and indicated a high level of MC (56 of 96 patients) in the first year post-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…the treatment of choice for many haematological disorders, can now be monitored successfully using DNA probes (Blazar et al, 1985: Knowlton et al, 1986. Recent studies have indicated that a mixed chimaeric state may occur, particularly following T cell depleted BMT (Hill et al, 1986;Petz et al, 1987;deWitte et al, 1987;Bretagne et al, 1987;Bertheas et a1, 1988). The influence of a mixed chimaeric state on subsequent graft rejection or relapse is as yet unknown.…”
mentioning
confidence: 99%
“…In the present study, we investigated whether chimerism patterns during the early post‐transplantation period may be used to predict the occurrence of severe acute GVHD after SCT. Several studies have shown that MC is correlated to a lower risk for developing moderate to severe acute GVHD after allogeneic SCT (5, 16), especially for patients transplanted for aplastic anemia (7, 17). We hypothesized that the clearance rate of host T cells between days 7 and 10 may be used to evaluate and monitor the recipient specific alloreactivity of donor T cells in vivo irrespective of diagnosis and pre‐treatment regimens.…”
Section: Discussionmentioning
confidence: 99%